MENINGKATKAN KREATIFITAS DAN INOVASI MELALUI PERMAINAN MAKE SOMETHING BEAUTIFUL - Paramita Nuraini; Subiyanto Subiyanto; Nofi Nur Yuhenita (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2020)
Abstract: The low creativity of students at Muhammadiyah High School in Magelang is the background in this service. This lack of creativity is related to creativity in thinking and creativity. Many students do not participate in teaching and learning activities as much as passive and monotonous students in learning. This dedication uses innovative Guidance Counseling media that is using the game "Make Something Beautiful". The target of this service is Muhammadiyah 1 High School students in Magelang City. Assistance is done by devotees to monitor the extent to which this dedication can increase student creativity. in the first stage which covers the Importance of Creativity for Students and Impacts for someone who lacks creativity, students begin to understand the importance of creativity and innovation in this 4.0 era.Keywords: innovation creativity; make something beautiful.  Abstrak: Rendahnya kreativitas siswa di SMA Muhammadiyah Magelang ini terkait degan kreativitas berpikir dan kreativitas bersikap. Banyak siswa yang kurang berpartisipasi dan kepercayaan diri dalam kegiatan belajar mengajar seperti halnya siswa pasif dan monoton dalam pembelajaran. Pengabdian ini menggunakan media Bimbingan Konseling yang inovatif yakni mengggunakan permainan “Make Something Beautiful”. Target dari pengabdian ini adalah siswa SMA Muhammadiyah 1 Kota Magelang. Pendampingan dilakukan pengabdi untuk memantau sejauh mana pengabdian ini dapat meningkatkan kreatifitas siswa. pada tahap pertama yang meliputi Pentingnya Kreatifitas Bagi siswa dan Dampak Bagi seseorang yang tidak memiliki kreatifitas, siswa mulai memahami pentingnya kreatifitas dan inovasi dalam era 4.0 ini.Kata kunci: inovasi ; kreativitas; make something beautiful.